2019
DOI: 10.7150/jca.28919
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants and Expression of Cytochrome p450 Oxidoreductase Predict Postoperative Survival in Patients with Hepatitis B Virus-Related Hepatocellular Carcinoma

Abstract: Our current study investigates the prognostic values of genetic variants and mRNA expression of cytochrome p450 oxidoreductase ( POR ) in hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC). A total of 19 candidate single nucleotide polymorphisms (SNPs) located in the exons of POR were genotyped using Sanger sequencing from 476 HBV-related HCC patients who underwent hepatectomy between 2003 and 2013. The mRNA expression of POR in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Although there have been extensive studies on various genetic variations associated with either susceptibility or progression of HCC [ 33 ], few studies have been performed regarding POR polymorphisms, and with limited polymorphic sites. To date, only POR A503V has been confirmed as an HCC susceptibility polymorphism [ 20 ]. Here we report the novel finding that the POR rs10459732 ( G > A ) polymorphism is correlated with decreased susceptibility to HCC and prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been extensive studies on various genetic variations associated with either susceptibility or progression of HCC [ 33 ], few studies have been performed regarding POR polymorphisms, and with limited polymorphic sites. To date, only POR A503V has been confirmed as an HCC susceptibility polymorphism [ 20 ]. Here we report the novel finding that the POR rs10459732 ( G > A ) polymorphism is correlated with decreased susceptibility to HCC and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…POR gene knock-out or liver-specific deletion has demonstrated to be lethal in the embryonic stage and causes a severe disruption of hepatic drug metabolism. In addition to the widespread expression of POR in multiple normal and tumor tissues [ 20 , 21 ], the POR gene is highly polymorphic, making it possible that POR variations contribute to cancer risk, either by changes in the metabolic activation of environmental carcinogens or by affecting the electron transfer process and metabolic activity of CYP enzymes [ 22 ]. Therefore, it is reasonable to study in detail POR polymorphisms and HCC susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…POR (cytochrome P450 oxidoreductase) is a flavoprotein which subserves several microsomal enzymatic reactions, most notably those deputized to drug metabolism and steroid biosynthesis [ 20 ]. In the context of adrenal steroidogenesis, POR contributes to 21 hydroxylase, 17 hydroxylase, and 17,20 lyase activity; indeed, mutations in POR may lead to sexual ambiguity and adrenal insufficiency, i.e., Antley–Bixler syndrome with genital abnormalities and disordered steroidogenesis (OMIM 201750) [ 9 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the rs1057868 polymorphism leads to an alanine-to-valine switch (i.e., p.A503V) and has been the focus of several studies under the moniker POR*28 . Studies in Asian as well as other populations have revealed an association of the variant with bladder cancer [ 32 ], post-kidney transplant diabetes [ 33 ], and hepatitis B virus-related hepatocellular carcinoma [ 20 ]. A small study evaluated p.A503V in 17 patients with either classic or non-classic adrenal hyperplasia [ 34 ], but was clearly underpowered to detect any association.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well known that single nucleotide polymorphisms (SNPs), an important form of genetic variants, may play an important role in prognosis of cancers including HCC [6][7][8] . Increasing evidence indicates that SNPs may affect the outcome of the patients with HCC, which have been used as biomarkers for predicting outcome of the patients with HCC [9,10] . However, previous genome-wide association study (GWAS) focused mainly on the SNPs with the strict P values of 5×10 − 8 , the vast majority of the identi ed top SNPs lack functional annotations [11] .…”
Section: Introductionmentioning
confidence: 99%